Território em ebulição: periferia, cultura e memória no noroeste paulistano de Perus - Marques, Raphael Pereira (2021)
The present dissertation proposes to analyze certain relations that are established in the peripheries of the city of São Paulo between its residents, social movements - with emphasis, more recently, for collectives in the field of culture - and the memories that are part of their territories. From the participation of the research and the researcher with political subjects from different generations in the northwest of Perus, sharing experiences and knowledge, we seek to understand how the memory of this territory is related, signified and mobilized, considering the "roughness" that marked it, as this is the case of the memory of their workers' struggle. It is necessary to understand that, in the urban context, narratives around the memory of peripheral territories tend to be disregarded and made invisible, given the hegemonic narrative about the memory of the city, dominated by the productive process. However, experiences such as those in Perus and northwestern São Paulo, as well as other social movements on the outskirts of the city, have established different relationships with the memory of their territories, of the struggles and mournings that existed there. Thus, it is possible that other actions and different meanings are created with regard to this peripheral social memory, making it, for example, an instrument of mobilization, political action and territorial development based on its cultural heritage